2020
DOI: 10.1371/journal.pone.0237787
|View full text |Cite|
|
Sign up to set email alerts
|

Translating drug resistant tuberculosis treatment guidelines to reality in war-torn Kandahar, Afghanistan: A retrospective cohort study

Abstract: Introduction Afghanistan is affected by one of the world's longest protracted armed conflicts, frequent natural disasters, disease outbreaks and large population movements and it suffers from a high burden of tuberculosis (TB), including rifampicin-resistant TB (RR-TB). The study shows Mé decins Sans Frontières' experiences with care for patients with RR-TB in Kandahar Province. We describe the uptake of RR-TB treatment, how World Health Organisation criteria for the choice between the short and an individuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Five studies that provided socioeconomic or psychosocial support during treatment reported treatment success among at least 71% of children and adolescents with tuberculosis. 55 58 , 62 …”
Section: Resultsmentioning
confidence: 99%
“…Five studies that provided socioeconomic or psychosocial support during treatment reported treatment success among at least 71% of children and adolescents with tuberculosis. 55 58 , 62 …”
Section: Resultsmentioning
confidence: 99%
“…Since 2016, in collaboration with the National Tuberculosis Control Programme (NTP), Médecins Sans Frontières (MSF) has been providing RR‐TB care in Kandahar, Afghanistan [ 9 ]. Afghanistan is affected by a protracted conflict.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that RR‐TB can be successfully treated in a complex setting like Kandahar but might still be affected by high attrition rates [ 9 ]. We concluded that our programme needed to adopt strategies to improve outcomes along with the cascade of care and increase the acceptability of treatment delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, 1.6 million TB-associated deaths occurred (Gupta et al, 2019), and it has also been suggested to be a major reason of death-related to antimicrobial resistance as well (Mesic et al, 2020). TB-infected individuals, if left untreated may lead to mortality rates of up to 40% (Suresh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%